“Double awareness”—adolescents and young adults coping with an uncertain or poor cancer prognosis: A qualitative study - Burgers, Vivian W. G.; van den Bent, Martin J.; Rietjens, Judith A. C.; Roos, Daniëlle C.; Dickhout, Annemiek; Franssen, Suzanne A.; Noordoek, Marloes J.; van der Graaf, Winette T. A.; Husson, Olga (Frontiers in Psychology, 2022)
Introduction: AYAs with an uncertain or poor cancer prognosis (UPCP) are confronted with ongoing and unique age-specific challenges, which forms an enormous burden. To date, little is known about the way AYAs living with a UPCP cope with their situation. Therefore, this study explores how AYAs with a UPCP cope with the daily challenges of their disease. Method: We conducted semi-structured in-depth interviews among AYAs with a UPCP. Patients of the three AYA subgroups were interviewed (traditional survivors, new survivors, low-grade glioma survivors), since we expected different coping strategies among these subgroups. Interviews were analyzed using elements of the Grounded Theory by Corbin and Strauss. AYA patients were actively involved as research partners. Results: In total 46 AYAs with UPCP participated, they were on average 33.4 years old (age range 23-44) and most of them were female (63%). Most common tumor types were low-grade gliomas (16), sarcomas (7), breast cancers (6) and lung cancers (6). We identified seven coping strategies in order to reduce the suffering from the experienced challenges: (1) minimizing impact of cancer, (2) taking and seeking control, (3) coming to terms, (4) being positive, (5) seeking and receiving support, (6) carpe diem and (7) being consciously alive. Conclusion: This study found seven coping strategies around the concept of ‘double awareness’ and showcases that AYAs are able to actively cope with their disease but prefer to actively choose life over illness. The findings call for CALM-therapy and informal AYA support meetings to support this group to cope well with their disease.